Endothelial Progenitor Cell Function Inversely Correlates With Long-term Glucose Control in Diabetic Patients: Association With the Attenuation of the Heme Oxygenase-Adiponectin Axis - Issan, Yossi (Can J Cardiol, 2012)
BACKGROUND: Endothelial progenitor cells (EPCs) are attenuated, both in number and functionality, in animal models of chronic cardiovascular and metabolic disorders. This effect has subsequently been linked to the aggravation of long-term morbidity and mortality associated with such disorders. The objective was to examine EPC number and survival in chronic diabetic vs nondiabetic patients in conjunction with the examination of their redox, inflammatory, and antioxidant defense system (Nrf2 genes) status in serum and visceral fat. METHODS: Visceral adipose tissue from diabetic and nondiabetic patients undergoing coronary artery bypass graft surgery was analyzed for Nrf2-dependent genes. Oxidative stress was evaluated using thiobarbituric acid-reactive substance assay (TBARS). Peripheral blood, collected 1 day prior to surgery, was evaluated for inflammatory cytokines and EPCs. RESULTS: When compared with controls (P < 0.05), results of the thiobarbituric acid-reactive substance assay were higher in diabetic patients. Although Nrf2-dependent antioxidant proteins (thioredoxin-1 [Trx-1], nicotinamide adenine dinucleotide phosphate [NAD(P)H] qui-none oxidoreductase [NQO1], glutathione S-transferase [GST]) were upregulated, heme oxygenase (HO-1) and adiponectin protein expression were lower in the diabetic group (P < 0.05). Serum levels of bilirubin were lower (P < 0.005) while the levels of inflammatory cytokines were higher in diabetic patients (P < 0.05). EPC levels and their colony forming units were significantly lower (P < 0.05) with reduced viability in diabetic patients as compared with nondiabetic patients. CONCLUSIONS: These results demonstrate for the first time that in diabetic patients, there is an inadequate heme oxygenase-adiponectin axis response, which could compromise the compensatory antioxidant and anti-inflammatory effects consequently contributing toward EPC dysfunction in these patients.